A novel lonidamine derivative targeting mitochondria to eliminate cancer stem cells by blocking glutamine metabolism - Qiang Wang; Shiyou Li; Chen Xu; Ao Hua; Chong Wang; Yuxuan Xiong; Qingyuan Deng; Xiang Chen; Tian Yang; Jiangling Wan; Ze-yang Ding; Bi-xiang Zhang; et al. (Elsevier, 2023)
Cancer stem cells (CSCs) have been blamed as the main culprit of tumor initiation, progression, metastasis, chemoresistance, and recurrence. However, few anti-CSCs agents have achieved clinical success so far. Here we report a novel derivative of lonidamine (LND), namely HYL001, which selectively and potently inhibits CSCs by targeting mitochondria, with 380-fold and 340-fold lower IC50 values against breast cancer stem cells (BCSCs) and hepatocellular carcinoma stem cells (HCSCs), respectively, compared to LND. Mechanistically, we reveal that HYL001 downregulates glutaminase (GLS) expression to block glutamine metabolism, blunt tricarboxylic acid cycle, and amplify mitochondrial oxidative stress, leading to apoptotic cell death. Therefore, HYL001 displays significant antitumor activity in vivo, both as a single agent and combined with paclitaxel. Furthermore, HYL001 represses CSCs of fresh tumor tissues derived from liver cancer patients. This study provides critical implications for CSCs biology and development of potent anti-CSCs drugs.